2010
DOI: 10.1002/pssa.200824482
|View full text |Cite
|
Sign up to set email alerts
|

Faceting of twin grain boundaries in polysilicon films

Abstract: The faceting of grain boundaries (GB) under annealing in phosphorus‐doped polysilicon films, produced by low‐pressure chemical vapor deposition, has been investigated by transmission electron microscopy. It has been shown that the facet types and facet density depend on annealing temperature. It has been found that GB facets are generally parallel with close‐packed planes in coincidence site lattice. A correlation between GB faceting and grain‐growth mechanisms has been considered. It has been shown that facet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Upon cooling below the roughening temperature, the facet appears again but with a certain hysteresis of about 5 K [125]. The CSL facets forming first-order ridge with each other or with rough GB portions were observed not only in metals, but also in polysilicon [126,127], GaN [128], PbTe [129], WC [130] and texturally equilibrated rocks [131].…”
Section: Faceting-roughening Of First and Second Ordersmentioning
confidence: 94%
See 1 more Smart Citation
“…Upon cooling below the roughening temperature, the facet appears again but with a certain hysteresis of about 5 K [125]. The CSL facets forming first-order ridge with each other or with rough GB portions were observed not only in metals, but also in polysilicon [126,127], GaN [128], PbTe [129], WC [130] and texturally equilibrated rocks [131].…”
Section: Faceting-roughening Of First and Second Ordersmentioning
confidence: 94%
“…If all GBs have a rough structure, then a nearly isotropic normal grain growth occurs. The abnormal grain growth is observed to occur when all or a fraction of the GBs are faceted [126,160,[173][174][175][176][177][178][179][180][181][182][183][184]. Below follows the detailed discussion of the works [126,160,[173][174][175][176][177][178][179][180][181][182][183][184].…”
Section: Faceting-roughening Of Low-angle Grain Boundariesmentioning
confidence: 99%
“…Nanocrystalline silicon, or simply nanosilicon, is widely used in modern integrated electronics [1,2] and as a promising material for solar cells [3,4]. It is known that the physical properties of silicon films strongly depend on the conditions of their growth and internal parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the conditions of growth of the nanocrystalline silicon films can affect notably their internal structure. On the other hand, the grain size determines the electrical properties of the films, because the grain boundaries are potential barriers for carriers [1,3]. The recent AFM-studies [10] have demonstrated that the grain size depends on the thickness of deposited films: the films with the thicknesses less than 50 nm contain the grains with the average size 25-30 nm, while the films thicker than 50 nm contain the grains as large as 180-200 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of silicon films, depending on deposition conditions and subsequent technological treatments, was studied in works [5][6][7][8][9][10][11][12][13][14] in detail. Various structural modifications of the films were revealednamely, equiaxial, fibrous, and dendritic -and conditions of their existence were determined [5].…”
Section: Introductionmentioning
confidence: 99%